A cross-sectional study of medial longitudinal arch development in children with different BMI - Chen, Jing; Tang, Li; Yang, Xiaoxuan; Tang, Jing; Cheng, Qingfeng; Zhao, Chen; Zhang, Han (Frontiers in Pediatrics, 2024)
Introduction The influence of excess weight on the development of children's feet remains a subject of debate. To further elucidate whether this relation occurs, this study compared arch morphology and flexibility in three groups of children: underweight, normal, and overweight. Methods In total, 1,532 children (807 boys, 725 girls; age range 7–11 years) participated in the study. The researchers measured the participants’ height and weight, calculated their body mass index, and categorized their weight status as underweight, normal weight, or overweight. A three-dimensional foot model was taken using a three-dimensional plantar scanner under non-weight-bearing and weight-bearing conditions to obtain arch morphometric indices (arch index and arch volume) and arch flexibility index (arch volume index). Results Analysis of the data showed that the arch index was higher in overweight children compared to underweight and normal weight children (p < 0.05), but the differences in arch volume and arch volume index in overweight children compared to underweight and normal weight children were not statistically significant (p > 0.05). All children were divided into flatfoot, normal, and pes cavus groups according to arch index, and the arch volume index was statistically significant (p < 0.01). Conclusions Overweight was not absolutely associated with arch structure and arch flexibility in children from a three-dimensional perspective. Arch development is a long-term process, and it is not clear whether being overweight has an effect on soft tissue or bone formation. Future studies will focus on the effects of long-term overweight on foot structure and arch flexibility in children.